Reconstructing Legal Protection for Deepfake Victims in Indonesia - Fathah Oscar; Femmy Silaswaty; Hanuring Ayu Ardhani Putri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rapid advancement of artificial intelligence (AI), particularly deepfake video technology, presents significant challenges to the protection of privacy, digital identity, and legal certainty. These challenges are exacerbated by the absence of a comprehensive legal framework governing deepfakes under Indonesian law. This study aims to analyze the regulation of deepfake technology under the Electronic Information and Transactions (ITE) Law, the Personal Data Protection Law, and the Indonesian Criminal Code; evaluate the effectiveness of existing legal protection for deepfake victims; and formulate a cyber law–based legal protection model. This research employs a normative legal methodology using qualitative analysis through statutory, conceptual, case, and comparative approaches. The findings indicate that the current legal framework remains fragmented and fails to provide a clear legal definition of deepfakes, standardized digital forensic procedures, an effective takedown-and-staydown mechanism, or an integrated system of victim protection. In response to these shortcomings, this study proposes a Legal Protection Model for Deepfake Video Victims Based on the Deepfake Life Cycle, integrating preventive, repressive, and restorative legal approaches. The proposed model is intended to strengthen legal certainty, safeguard digital identity, enhance the effectiveness of cyber law enforcement, and ensure comprehensive protection and recovery for victims of deepfake-related offenses.